2012
DOI: 10.1136/amiajnl-2011-000628
|View full text |Cite
|
Sign up to set email alerts
|

Physicians who use social media and other internet-based communication technologies

Abstract: The demographic and practice-related characteristics of physicians who use social networking websites, portable devices to access the internet, email to communicate with patients, podcasts, widgets, RSS feeds, and blogging were investigated. Logistic regression was used to analyze a survey of US primary care physicians, pediatricians, obstetrician/gynecologists, and dermatologists (N=1750). Reported technology use during the last 6 months ranged from 80.6% using a portable device to access the internet to 12.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 10 publications
3
52
2
Order By: Relevance
“…Surveys show that more than sixty per cent of Unites States physicians use social media or relevant participatory media to look for medical information and to communicate with peers. 1,2,4 Similarly, European physicians have also begun to embrace most social media tools. 3,5 The use of 4 smartphones and tablets has also increased significantly among physicians around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys show that more than sixty per cent of Unites States physicians use social media or relevant participatory media to look for medical information and to communicate with peers. 1,2,4 Similarly, European physicians have also begun to embrace most social media tools. 3,5 The use of 4 smartphones and tablets has also increased significantly among physicians around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Many physicians have now started to embrace most of the social media tools, either formally through their organizations or informally through personal use, and this has grown significantly in recent years. [1][2][3] For example, physician-only social networks such as Sermo, Ozmosis, and Medscape have attracted over 100,000 members each. Surveys show that more than sixty per cent of Unites States physicians use social media or relevant participatory media to look for medical information and to communicate with peers.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 Cooper et al reported that prevalence of utilizing Internet applications to aide their medical care is based on the demographics of physicians, with use being most associated with being a young physician in an academic institution. 7 Eltorai et al demonstrated that a major flaw of the information available, most notably from the American Academy of Orthopaedic Surgeons (AAOS), is the educational materials are written at a reading level that exceeds the reading level of the average patient. 8 Our finding that patients prefer a written handout also suggests that the health education materials patients find on the Internet do not improve their health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Published studies describing health professionals' use of blogs, Facebook, Twitter, and other social media outlets report that online posting of unprofessional content is common and includes violations of patients' privacy and confidentiality, as well as inappropriate language, sexually explicit material, and discriminatory statements. 3 Some 90% of recently surveyed executive directors of medical and osteopathic boards indicated that at least one of several types of online professionalism violations had been reported to their board. The most common of these were inappropriate patient communication of a sexual nature, use of the Internet for inappropriate practice such as prescribing without an established clinical relationship, and online misrepresentation of credentials.…”
mentioning
confidence: 99%
“…Certainly, Internet-based communication can improve health care delivery through increased access to care and improved perception of health care quality. 3 Blogging on patient and caregiver Web sites can also offer professional satisfaction and foster relationships that provide farreaching benefits.…”
mentioning
confidence: 99%